Pengaruh Training Program dan Work Interest terhadap Kinerja Karyawan dengan HR Development sebagai Variabel Intervening pada PT Perkebunan Nusantara XIV Unit Pabrik Gula Takalar - Aqwan Panji, iqbal_mustafa; Jafar, Akhmad (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
This research aims to examine the effect of training programs and work interest on employee performance with HR development as an intervening variable at PT. Perkebunan Nusantara XIV Takalar Sugar Factory Unit. The data source in this research comes from primary data, where the method for collecting data is using interviews and questionnaires which are distributed to all employees of PT. Perkebunan Nusantara XIV Takalar Sugar Factory Unit. The samples used were 126 samples. The data analysis technique in this research is using SPSS 21 using software. The results of this research show that the training program data shows that the training program and work interest variables have a significant effect on employee performance. The higher the implementation of the training program, the higher the employee performance, the data results show that the work interest variable has a positive effect so that there is employee performance. And the relationship between training programs and performance, this means that the existence of training programs can influence employee performance. Keywords: Trainning Program, Work Interest, Employee Performance and HR Development.